The Protection of Public Rights in Islamic Law: Harmonizing Maqāṣid al-Sharīʿah with Indonesia’s Positive Legal Framework - Indi Rahmat Hidayat; Sumarta; Rifqi Rifqi (Penerbit Hellow Pustaka, 2025)
This research examines the protection of public rights from the perspective of Islamic law, aiming to understand the relevance of Sharia principles within modern contexts and positive legal practices in Indonesia. The study is motivated by the existing gap between Sharia theory and the implementation of public rights, alongside the demands of globalization and international human rights standards that necessitate the harmonization of Islamic norms with national law. Utilizing a qualitative approach through library research and descriptive analysis, data were gathered from scientific journals, reference books, legal documents, and contemporary articles discussing Islamic law, maqāṣid al-sharīʿah, and public rights. An inductive analysis was performed to identify patterns, Sharia principles, and the relationship between individual rights and collective interests. The results indicate that public rights in Islamic law are deeply rooted in maqāṣid al-sharīʿah, which emphasizes the preservation of religion, life, intellect, progeny, and property. The principles of justice, public interest (maslahah), and social responsibility serve as the primary foundations for formulating public policy and protecting communal rights. Furthermore, this study identifies discrepancies between Islamic law and Indonesia's positive legal practices, particularly regarding education, healthcare, minority rights, and religious freedom, highlighting the need for integration with international human rights standards. In conclusion, the protection of public rights is a collective responsibility shared between the state and society. Integrating Sharia principles into public policy can enhance social justice, legal literacy, and community welfare. This research offers both academic and practical contributions to the development of modern Islamic legal theory, policy, and practice.